Cell wall methanol as a signal in plant immunity - Komarova, Tatiana V.; Sheshukova, Ekaterina V.; Dorokhov, Yuri L. (Frontiers in Plant Science, 2014)
Cell wall pectin forms a matrix around the cellulose–xyloglucan network that is composed of rhamnogalacturonan I, rhamnogalacturonan II and homogalacturonan (HG), a major pectic polymer consisting of α-1,4-linked galacturonic acids. HG is secreted in a highly methyl-esterified form and selectively de-methyl-esterified by pectin methylesterases (PMEs) during cell growth and pathogen attack. The mechanical damage that often precedes the penetration of the leaf by a pathogen promotes the activation of PME, which in turn leads to the emission of methanol (MeOH), an abundant volatile organic compound, which is quickly perceived by the intact leaves of the damaged plant and the neighboring plants. The exposure to MeOH may result in a “priming” effect on intact leaves, setting the stage for the within-plant and neighboring plant immunity. The emission of MeOH by a wounded plant enhances the resistance of the non-wounded, neighboring “receiver” plants to bacterial pathogens and promotes cell-to-cell communication that facilitates the spread of viruses in neighboring plants.